The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/978-3-642-15552-9_22
|View full text |Cite
|
Sign up to set email alerts
|

A Dual Theory of Inverse and Forward Light Transport

Abstract: A cornerstone of computer graphics is the solution of the rendering equation for interreflections, which allows the simulation of global illumination, given direct lighting or corresponding light source emissions. This paper lays the foundations for the inverse problem, whereby a dual theoretical framework is presented for inverting the rendering equation to undo interreflections in a real scene, thereby obtaining the direct lighting. Inverse light transport is of growing importance, enabling a variety of new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…This derivation makes explicit the connection between the iterative computation framework of Bimber et al (2006) and Bimber (2006) with known scene geometry and the stratified inversion framework of Ng et al (2009) with only light transport measurement as input. Second, we show a Neumann interpretation for the stratified inverses in terms of physical bounces of light, which brings out an interesting correspondence between the forward and the inverse light transport (a brief summary of this result is described by us in Bai et al (2010), but this paper presents the full derivation and analysis.) Although Seitz et al (2005) has showed that inverse light transport can be used for separating light bounces in forward light transport, the physical meaning of the polynomial terms in inverse light transport is novel.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…This derivation makes explicit the connection between the iterative computation framework of Bimber et al (2006) and Bimber (2006) with known scene geometry and the stratified inversion framework of Ng et al (2009) with only light transport measurement as input. Second, we show a Neumann interpretation for the stratified inverses in terms of physical bounces of light, which brings out an interesting correspondence between the forward and the inverse light transport (a brief summary of this result is described by us in Bai et al (2010), but this paper presents the full derivation and analysis.) Although Seitz et al (2005) has showed that inverse light transport can be used for separating light bounces in forward light transport, the physical meaning of the polynomial terms in inverse light transport is novel.…”
Section: Introductionmentioning
confidence: 65%
“…This is done using Jacobi iteration on the projector input vector, with the form factor matrix derived from the scene geometry. In the case of unknown scene geometry, but given the light transport of the scene, we showed in Bai et al (2010) that projector radiometric compensation can be similarly computed iteratively. These approaches relate closely to the radiosity method for diffuse global illumination in forward rendering (Hanrahan et al, 1991;Gortler et al, 1993).…”
Section: Radiometric Compensationmentioning
confidence: 99%
“…The first approach solves Eq. 1 as a system of linear equations [1]. Efficient methods of this approach are the Jacobi method and the Gauss-Seidel method that involves iterative vector-matrix multiplication.…”
Section: Inverse Light Transport Computationmentioning
confidence: 99%
“…It is common that f-LTM T under focused light sources such as light pixels of a projector are diagonally dominant 1 [1,8,23]. An example of such f-LTM is shown in Fig.1(a) with another one shown in Section 3 of the supplementary.…”
Section: Invertibility Of F-ltm and Compressibility Of I-ltmmentioning
confidence: 99%
See 1 more Smart Citation